ИНФЕКЦИОННЫЙ ЭНДОКАРДИТ КАК РЕДКОЕ ОСЛОЖНЕНИЕ ЦИРРОЗА ПЕЧЕНИ (ОПИСАНИЕ КЛИНИЧЕСКОГО СЛУЧАЯ) - Г. И. Сторожаков; Е. А. Луговкина; Л. Ю. Ильченко; И. Г. Федоров; С. Д. Косюра; Н. Н. Мерзликина; Е. И. Пожарицкая; Н. В. Петренко; Е. А. Степанова (Архивъ внутренней медицины)
The complications caused by the infection are observed among 38–47% of cirrhosis patients and directly provoke death by about a quarter of patients. Infective endocarditis occurs among 0.34–1.33%. The diagnostics of infective endocarditis remains a challenge for general practitioners. This article describes the clinical course of cirrhosis, complicated by endocarditis.